Abū Bakr ibn Abī Shaibah (235) as a Figure on the Field of Hadith | أبو بكر بن أبي شيبة (345 هـ) شخصية حديثية - Muhammad Khairul Mustaghfirin (Al-Zahra : Journal for Islamic and Arabic Studies, 2014)
Abdullāh b. Muhammad b. Abī Shaibah al-Kūfī (d 235 AH), was a famous ḥāfiẓ(memorizer of hadith). He received the hadith from Abu al-Aḥwaş al-Ḥanafī, Sharīk al-Nakhaʻī, Hushaim b. Bashīr, Wakīʻ b. al-Jarrāḥ, Ibn Uyainah, Ibn Mahdī, Yaḥyā b. Saʻīdal-Qațțān and others. Among those who received the hadith from him are al-Bukhārī,Muslim, Abū Dāwud and Ibn Mājah. Among those who narrated hadith to him throughAhmad are al-Nasāʻī, Ahmad b. Ḥanbal, Abu Zurʻah, Abu Ḥātim. The scholars agreedthat Abū Bakr b. Abī Shaibah is person who has strong memorizing, he praised by manyscholars. Abū al-Ubaid al-Qāsim said, "The top of knowledge held by four persons, wereIbn Abī Shaibah as a skillful people in mentioning hadith, Ahmad is the most intelligentpeople understand the hadith, Yaḥyā is the most people who collect hadith and Alī b. al-Madīnī is the pious people in hadith. And the most memorized person when there was areviewing is Abū Bakr b. Abī Shaibah. While Ibn Ḥibbān said, "Ibn Abī Shaibah was aḥāfiẓ who has strong memorizing, he's one of the scholars who wrote the hadith, collectsand assembles books, also doing reviewing of hadis. He was the most scholars and ḥāfiẓfor hadīth maqțūʻ.